Thermochemical conversion of waste hemp textiles into hierarchical porous carbons for CO2 capture: Kinetic insights and structure–property relationships - Zihan Wang; Tianxin Li; Boling Song; Shoujun Liu; Sha Li (AIP Advances)
This study pioneers the sustainable conversion of waste hemp textiles into hierarchical porous carbons for CO2 capture through kinetics-guided pyrolysis. Thermogravimetric analysis coupled with model-free kinetic methods (Flynn–Wall–Ozawa and Kissinger–Akahira–Sunose) quantitatively revealed a three-stage decomposition mechanism, demonstrating exceptional consistency in apparent activation energies (220.0–221.2 kJ/mol). Strategic temperature modulation (500–900 °C) enabled precise control over carbon nanostructures, as evidenced by multi-scale characterization: X-ray diffraction and Raman spectroscopy confirmed temperature-dependent graphitization (ID/IG: 1.34 → 1.04), while nitrogen physisorption unveiled tunable micro–mesoporous architectures (SBET: 117–476 m2/g). The 800 °C-derived carbon exhibited optimal CO2 adsorption, directly correlating with its microporous dominance (<1 nm, 78% contribution). Crucially, this work establishes structure–property relationships between pyrolysis conditions (residence time/temperature), carbon matrix evolution, and gas capture performance, achieving 32.4% carbon retention from waste feedstock. The dual innovation lies in first application of advanced kinetic modeling to textile waste carbonization and mechanistic elucidation of micropore-driven physisorption, providing a scalable paradigm for converting agricultural residues into high-value environmental materials.